A preliminary approach for comparative life cycle assessment of flexible and rigid pavements-A case study - Varun B.S.S.; Choudhary J.; Gupta A. (My University, 2025)
Climate change is one of the important terms that has been gaining importance in everyday life. Construction and maintenance of the pavements, and their materials, had a significant role in environmental pollution. Therefore, choosing a suitable type of pavement, is necessary to reduce the environmental impacts. This study analyzed the relative environmental impacts caused by the flexible and rigid pavements and to identify the best suitable pavement having minimal environmental damage. This study includes the design of a flexible and rigid pavements, for a traffic load of 100 msa (million standard axles) and the soil CBR as 8%. A double lane of unit km is taken for evaluation. A preliminary approach for comparative life cycle assessment (LCA) was performed on the pavements, using ReCiPe 2016 Midpoint (H) method by following a cradle to gate approach. The obtained data is the number of environmental impacts caused by various factors, released during the construction of the pavement. The data were analyzed and compared. In general, it was observed that the rigid pavement construction involves a release of, a comparatively large amount of greenhouse gases and the usage of natural resources, which resulted in high environmental pollution. Therefore, it can be concluded that the flexible pavements can be preferred over rigid pavements to reduce the environmental damage and to have a good sustainable life of living for similar conditions of traffic and soil subgrade. © 2022 the Author(s).